Developmental Psychopathology 2016
DOI: 10.1002/9781119125556.devpsy123
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Data Analysis for Research in Developmental Psychopathology

Abstract: Researchers from many disciplines have increasingly called for changes in research practices to be more transparent and rigorous. One of the changes prominently discussed is the utilization of quantitative research synthesis from multiple single studies, which we broadly refer to as integrative data analysis (IDA). The present chapter discusses how IDA can be particularly helpful for research in developmental psychopathology. We provide a broad overview of evidence‐based quantitative approaches, covering diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 160 publications
0
9
0
Order By: Relevance
“…IDA studies pool raw participant-level data from multiple studies and analyze them as a single data set, and can provide many of the same benefits of multi-site trials at a fraction of the cost if study-level heterogeneity can be properly accounted (see Hussong, Curran, & Bauer, 2013; Mun et al, 2015; Mun, Jiao, & Xie, 2016 for detailed discussions). Project INTEGRATE includes data from 24 independent trials at U.S. colleges.…”
Section: Methodsmentioning
confidence: 99%
“…IDA studies pool raw participant-level data from multiple studies and analyze them as a single data set, and can provide many of the same benefits of multi-site trials at a fraction of the cost if study-level heterogeneity can be properly accounted (see Hussong, Curran, & Bauer, 2013; Mun et al, 2015; Mun, Jiao, & Xie, 2016 for detailed discussions). Project INTEGRATE includes data from 24 independent trials at U.S. colleges.…”
Section: Methodsmentioning
confidence: 99%
“…The mediator variable, PBS, was measured using five different scales across the original studies, which were subsequently harmonized and made commensurate by using a generalized partial credit model (Muraki, 1992), which is an extension of the hierarchical two-parameter logistic item response theory (2-PL IRT) model that we reported for alcohol-related problems (Huo et al, 2015). The measurement work to establish PBS trait scores can be found in Mun et al (2015Mun et al ( , 2016. With respect to the motivating data, studies 2, 8a, 8b, 8c, and 9 used the 10-item Protective Behavioral Strategies (PBS; American College Health Association, 2001) measure; studies 16, 18, and 21 used the 15-item Protective Behavioral Strategies Scale (PBSS; Martens et al, 2005); and studies 12 and 22 used the sevenitem Drinking Restraining Strategies (DRS; Wood et al, 2007) measure.…”
Section: Motivating Data: the Project Integrate Studymentioning
confidence: 99%
“…With respect to the motivating data, studies 2, 8a, 8b, 8c, 9, 16, and 21 used the Rutgers Alcohol Problem Index (RAPI; White & Labouvie, 1989); studies 8a, 8b, 8c, 9, 12, 16, and 22 used the Young Adult Alcohol Problems Screening Test (YAAPST; Hurlbut & Sher, 1992); study 12 also used the Alcohol Dependence Scale (Skinner & Allen, 1982;Skinner & Horn, 1984); study 18 used the Brief Young Adult Alcohol Consequences Questionnaire (BYAACQ; Kahler et al, 2005); and study 21 used the Alcohol Use Disorders Identification Test (AUDIT; Saunders et al, 1993). For readers interested in the technical details regarding how the measures of PBS and alcohol problems used in the motivating data were made commensurate, the harmonization work is discussed extensively in earlier reports (Huo et al, 2015;Mun et al, 2015Mun et al, , 2016Mun et al, , 2019.…”
Section: Motivating Data: the Project Integrate Studymentioning
confidence: 99%
“…To understand how between-study differences are modeled in meta-analysis, one must also appreciate the difference between fixed-effects and random-effects models, the two most common models for metaanalysis (see also Mun, Jiao, & Xie, in press for a review). Under the fixed-effects model, we assume there is one true effect size θ underlying all studies and thus any differences in observed effect sizes are due to sampling error si2 , which varies from study to study.…”
Section: Review Of the Foxcroft Et Al (2014) Meta-analysismentioning
confidence: 99%